APPLICATION OF THE EXPERIENCE OF EUROPEAN COUNTRIES IN THE IMPLEMENTATION OF FINANCIAL CONTROL OVER THE ACTIVITIES OF TERRITORIAL COMMUNITIES IN UKRAINE - Shchur , R.I.; Plets, I.I.; Matskiv , V.V.; Biloshkurska , N.V. (The actual problems of regional economy development, 2022)
Possibilities of practical application of the experience of EU countries in the modernization of financial control are identified. In contrast to existing approaches, it involves financial control in the implementation of targeted programs of united territorial communities in Ukraine in three areas: financial control during the formation and adjustment of target programs of the united territorial community (provides analysis of the need to implement the program, verification of compliance and volume of financial support, analysis of resource adequacy, analysis of the dynamics of indicators of target programs); 2) financial control over the expenditures of the program budget during the implementation and financing of targeted programs of territorial communities (includes verification of the validity of financial expenditures, analysis of the implementation of the main measures of the program, verification of the report on the program); 3) financial control of the results of the implementation of target programs of the united territorial communities (covers the comparison of actual indicators of program implementation costs with planned, analysis of the degree of achievement of program goals, analysis of the dynamics of financial indicators of the target program). The purpose of the article is to apply the experience of European countries in the implementation of financial control over the activities of territorial communities in Ukraine in the context of administrative and territorial reform. Achieving the goal is ensured by using methods such as analysis and synthesis, induction and deduction, generalization and scientific abstraction. The need to highlight and disseminate the best management practices, the formation of appropriate information space and the use of modern information systems and technologies to provide opportunities for monitoring, data processing, situation analysis is established. This would allow to reduce the management costs of local communities, accelerate the monitoring and response to exogenous and endogenous factors, improve the quality of the management process, strengthen the relationship of governing bodies with the community and the influence of community members on the management process.